Composição faunística de insetos predadores em fragmento florestal e em área de hortaliças na região de Jaboticabal, estado de São Paulo - Cividanes, Francisco Jorge [UNESP]; De Paula Souza, Vanderlei [UNESP]; Sakemi, Luciano Kenji (Universidade Estadual de Maringa, 2003)
A population survey was carried out in a forest fragment and in an area of vegetables, from November/1996 to February/1998, aiming to determine the predator insect species and the influence of abiotic factors. The samples were taken weekly by light traps. The results were evaluated using faunistic analysis and simple correlation with temperature, relative humidity and rainfall. In the forest fragment higher similarity in the abundance of species was observed comparing to the area of vegetables, but the largest number of captured individuals (95%) occurred in this last habitat. Metius sp., Polpochila impressifrons (Dej.), Eulissus sp. and Doru sp. were predominant species in both areas, evidencing they may play an important role as pest predators in areas of vegetables. Arthrostictus speciosus (Dej.) and Leptotrachelus sp. predominated in the forest fragment, and the same was observed with Paederus sp. in the vegetable area. This species is probably adapted for open and hot places, while A. speciosus and Leptotrachelus sp. can be adapted for dark and humid places of forests.
Faunal composition of predator insects in forest fragment and area of vegetables in Jaboticabal region, state of São Paulo, Brazil
Keywords: Biological control; Carabidae; Light trap; Population dynamics; biological pest control; Brazil; forest; insect control; nonhuman; population dynamics; predation; vegetable; Doru; Hexapoda; Insecta; Leptotrachelus; Metius; Paederus; Polpochila